ACCESSIBILITY OF HIGHER EDUCATION FOR RURAL SCHOOL GRADUATES: AN ANALYSIS OF EDUCATIONAL TRAJECTORIES BASED ON STATISTICAL DATA - Shakenov D. S.; Sarybayeva I. S. (Foundations and Trends in Modern Learning, 2025)
This study examines the accessibility of higher education for graduates of rural schools in Kazakhstan by analyzing national statistical data on school completion, university enrollment, and the distribution of state-funded grants. Using a quantitative design based on official datasets from the Bureau of National Statistics, the research identifies persistent disparities between rural and urban students and reveals substantial regional variation in educational outcomes. The findings show that although rural quotas and targeted state policies expand formal opportunities for rural applicants particularly in fields linked to rural development these measures are insufficient to eliminate structural inequalities rooted in school quality, digital infrastructure, socio-economic conditions, and institutional geography. The study highlights that rural students continue to face significant disadvantages in standardized exam performance, access to preparatory resources, and the financial burden associated with studying in major urban centers. These results underscore the complex interaction of structural, socio-economic, and policy-related factors shaping rural students’ educational trajectories. The study concludes that improving rural access to higher education requires a multi-dimensional approach that combines quota mechanisms with investments in rural school infrastructure, digital inclusion, financial support programs, and regional higher-education development strategies